Permodelan Numerik Aliran Angin Pada Jalan Antara Bangunan Tinggi Dengan Modifikasi Sudut Datang - Priambodo, Doni; Sanjaya, Yongky; Sarli, Prasanti Widyasih; Setio, Herlien Dwiarti (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
In fluid dynamics analysis, one of the things to do is to perform numerical modeling validated on the resultsof experimentation. In numerical modeling of wind flow there are several forms of modeling used includingRANS, LES, DNS, etc. where the modeling has its own advantages and disadvantages. Among these models,RANS is a model that has the cheapest computer expense compared to other models so that it has the highestworkability. Therefore, rans method testing (Reynolds Averaged Navier Stokes) was conducted to determinethe capability of turbulence models in checking wind speed contours on the road between 4 simplesymmetrical tall buildings with 0o, 30o, and 45o attack an gles validated with the results ofexperimentation. This research was conducted using RANS modeling (Reynolds Averaged Navier Stokes) andstandard turbulence model k-ε and validated using Low Speed Wind Tunnel and PIV (Particle ImageVelocimetry). According to the results of the test, U/Uo wind speed conditions obtained in wind modelingwith RANS and k-ε standards have errors that are still acceptable.